TRAINING PERAN PUBLIK DAN DOMESTIK PEREMPUAN PERSPEKTIF AL-QUR’AN DI YAYASAN BALQIS - Ahmad Thib Raya; Nurbaiti Nurbaiti; Ikrima Nisdi; Qurrah A’yuniyyah; Salman Faris; Hirman Jayadi (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2024)
The interpretation of the Qur’an has undergone dynamic development in line with the growing awareness among Muslims of the importance of the principle of justice, particularly in the relationship between men and women. Within the development of contemporary Qur’anic thought, feminist exegesis has emerged as an approach that seeks to reconstruct perspectives on the sacred text by positioning women as active subjects in the interpretive process. This approach responds to the patriarchal bias that has shaped classical exegetical traditions, in which women are often portrayed in subordinate and marginalized roles. Amina Wadud is one of the central figures in feminist exegesis, offering a critical and contextual reading of the Qur’an. Through a hermeneutical approach that emphasizes the interrelation between text, context, and reader, Wadud highlights the importance of the Qur’an’s universal values such as tawḥīd (divine unity), justice, equality, and respect for human dignity as a foundation for building more just and equitable social relations. This study aims to examine Amina Wadud’s intellectual contributions to the development of feminist exegesis through a literature review of her major works, including Qur’an and Woman and Inside the Gender Jihad. Using a qualitative-descriptive method based on library research, this paper explores her methodology, thematic concerns, and the social and theological implications of her feminist readings. The findings indicate that the feminist approach developed by Wadud not only broadens the horizons of Qur’anic interpretation but also opens space for a more inclusive, just, and contextually grounded understanding. Her thought significantly contributes to shaping a more humanistic, socially responsive, and gender-equitable understanding of Islam